The effect of bushmeat consumption on migratory wildlife in the Serengeti ecosystem, Tanzania. Issue 2 (15th July 2014) - Rentsch, Dennis; Packer, Craig
Abstract: Bushmeat hunting is a threat to wildlife populations in many parts of sub-Saharan Africa, including to migratory wildebeest Connochaetes taurinus and other wildlife populations in the Serengeti ecosystem. Accurate assessments of offtake through bushmeat hunting are necessary to determine whether hunting pressure on the wildebeest population is unsustainable. We used a panel dataset of local bushmeat consumption to measure offtake of wildlife and examine the long-term threat to the Serengeti wildebeest population. Based on these data we estimate an annual offtake of 97, 796–140, 615 wildebeest (6–10% of the current population), suggesting that previous estimates based on ecological models underestimated the effect of poaching on these populations.